Perilaku Petani Dalam Penerapan Sistem Pertanian Organik Di Kelompok Tani Mertha Sarining Bhuana Desa Bangli Kecamatan Baturiti Kabupaten Tabanan - MANDALA, I DEWA GEDE WIRA SATRIA; SUARDI, I DEWA PUTU OKA; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023DO - 10.24843/JAA.2023.v12.i01.p14, 2023)
Behavior of Farmers in the Application of Organic Farming Systems in Mertha Sarining Bhuana Farmers Group Bangli Village, Baturiti District, Tabanan Regency Organic farming systems have a positive impact on the environment and farming activities compared to conventional farming. However, in reality, the application of organic farming systems has not been fully implemented, therefore it is necessary to have sufficient knowledge to form positive attitudes of farmers and good actions in an effort to implement organic farming systems in their own environment. This study aims to determine the level of knowledge, attitudes, and actions of farmers in the application of organic farming systems in the Mertha Sarining Bhuana farmer group, Bangli Village, Baturiti District, Tabanan Regency. Sampling with a saturated sampling method with the number of respondents 23 people. The data analysis method used is qualitative descriptive analysis. The results of the analysis show that the level of knowledge of farmers about organic farming systems is in the moderate category with a total score of 859, while the attitudes of farmers are in the agree on category with a total score of 1181, and the actions of farmers are in the sufficient category with a total score of 717. and the behavior of farmers regarding organic farming systems is in the moderate category. in the good category with a total score of 2,764. Based on the results of this study, the behavior of farmers is expected to support agricultural development by implementing organic farming systems in the surrounding environment.